Safari special edition killer instinct - Stanton, David L.; Ross, John; Merrill, Chris ([San Jose, Ca.] : Starcast, 1998)
A candid journey that takes you from the jungles of Africa and Australia to the Yukon frontier. Experience the human drama in their endless quest, tracking the most interesting and exotic animals alive
Title from container
Executive producer, Paul Sharratt ; camera, Jed Udall, John R. Peterson, Chris Merrill
Host: John Ross
VCD format
Keywords: Predatory animals; Predation (Biology)